Analysis Diachronic Swadesh Wordlist Between Ngapaknese and Javanese - Umi Mujiarni; Imam Qalyubi; Misrita (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2025)
The qualitative research entitled “Diachronic Analysis Swadesh Wordlist: Ngapak vs Java” will focus on examining historical linguistic changes and relationships between Ngapak and Javanese dialects using the Swadesh wordlist. The study will use a diachronic approach to analyze the evolution of vocabulary and phonological aspects over time, providing insight into the linguistic kinship and differences between these dialects. This research applies qualitative methods by utilizing historical-comparative linguistic approaches and corpus-based analysis to identify significant changes and retentions in core vocabulary. The results show that Ngapak dialect tends to retain more archaic phonological and lexical forms, while Standard Javanese undergoes innovation and simplification in a number of basic vocabularies. In addition, it was found that retention, innovation, and external influences distinguish the two dialects, both in terms of pronunciation and vocabulary selection. These findings enrich the understanding of the dynamics of Javanese language change, the importance of local dialect preservation, and contribute to the mapping of linguistic kinship in the Java region.